Ethnocultural wisdom and development of e-comic - Ermiana, Ida; Parwati, Ni Nyoman; Sudiarta, I Gusti Putu; Sudatha, I Gde Wawan (Institute of Advanced Engineering and Science, 2024)
Cultivating local cultural values by adapting to technological advances, found in digital comic learning media oriented towards local Sasak wisdom, provides ease of learning and communicative language and is easy to access but still needs to be improved. The research aims to develop digital comic media that is feasible, practical and effective, oriented towards Sasak local wisdom (e-kodisa). The development stage uses the stages of analysis, design, development, implementation and evaluation (ADDIE). The research results show that digital comic media oriented towards Sasak local wisdom from material experts in category 1 is feasible, and material experts in category 2 are possible. The assessment of digital comic media from Media expert 1 is in the attainable category, and media expert 2 is very doable. The evaluation of learning design experts and language experts is in the very decent category. Trials on students show that digital comic media is practical and can be used in learning. The results of the effectiveness test showed sig. (2-tailed)<0.05 Ho is rejected, and Ha is accepted, meaning a significant difference exists between the pretest and posttest averages. So, developing digital comic media oriented towards Sasak local wisdom is feasible, practical and effective.